Respuesta :

x=2 and y=(-2)

hope it helps...

Ver imagen Аноним
Hi1315

Answer:

y = ( -2 )

x = 2

Step-by-step explanation:

4x + y = 6 ⇒ ( 1 )

x - 2y = 6  ⇒ ( 2 )

x = 6 + 2y ⇒ ( 3 )

First, let us find the value of y.

For that, we can replace x with ( 6 + 2y ).

Let us use equation 1 for that.

4x + y = 6

4 ( 6 + 2y ) + y = 6

24 + 8y + y = 6

24 + 9y = 6

9y = 6 - 24

9y = -18

Divide both sides by 9.

y = -2

Now let us find the value of x by replacing y with -2.

For that let us take equation 3.

x = 6 + 2y

x = 6 + 2 × -2

x = 6 - 4

x = 2